VIRTUAL COUNSELING: EMBRACING VR TECHNOLOGY TO SUPPORT STUDENTS' PERSONAL AND SOCIAL DEVELOPMENT - Wulan, Werdining (Journal of Education Technology and Inovation, 2024)
Innovation in virtual reality (VR) technology offers promising solutions in the field of counseling. The use of VR in counseling sessions can create a safe, comfortable, and stigma-free environment for students. Many students feel reluctant or uncomfortable to engage in face-to-face counseling sessions, especially if they have sensitive or private issues, to fill this gap by systematically exploring the application of virtual counseling using VR technology has an impact on students' personal and social development. This study will use an experimental design. The research design of One Group Pretest-Posttest Design, the results of the One-Sample Test obtained a pretest t-value of 20.270, a posttest t-value of 21.172 and a significant value of 0.000, indicating a significant difference between Personal Development pretest and posttest in the class using VIRTUAL COUNSELING and a pretest t-value of 10.506, a posttest t-value of 22.936 and a significant value of 0.000, indicating a significant difference between Social Skills before and after VIRTUAL COUNSELING Overall, the results of this study indicate that virtual counseling using VR technology has great potential to support students' personal and social development comprehensively. And can help students develop communication, cooperation, and empathy skills, in a complex social environment